Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1007/s00520-007-0254-7
|View full text |Cite
|
Sign up to set email alerts
|

Dying at home or in an institution: perspectives of Dutch physicians and bereaved relatives

Abstract: Introduction Previous studies have shown that most people prefer to die at their own home. We investigated whether physicians or bereaved relatives in retrospect differently appreciate the dying of patients in an institution or at home. Materials and methods Of 128 patients with incurable cancer who were followed in the last phase of their lives, 103 passed away during follow-up. After death, physicians filled out a written questionnaire for 102 of these patients, and 63 bereaved relatives were personally inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 32 publications
3
27
0
Order By: Relevance
“…22 In another study, there was no indication that dying in an institution or at home involves major differences and quality of dying. 23 Both studies, however, did not analyze the real circumstances of death, which was the main aim of this observational study.…”
Section: Discussionmentioning
confidence: 99%
“…22 In another study, there was no indication that dying in an institution or at home involves major differences and quality of dying. 23 Both studies, however, did not analyze the real circumstances of death, which was the main aim of this observational study.…”
Section: Discussionmentioning
confidence: 99%
“…3 6 13-15 However, there is considerable variation between studies. A substantial number of people do not specify a preference, 16 and there is rarely an option for "it depends" or "does not matter." 17 The context and framing of the questions will shape the nature of responses, and studies vary in their design and quality.…”
Section: Is Place Of Death a Public Priority?mentioning
confidence: 99%
“…This of course can be accomplished in several care settings. For example, in a study of a cohort of 128 patients with incurable cancer, Van der Heide et al (2007) found no indication that dying in an institution or at home involve major differences in the process and quality of dying.…”
Section: 2mentioning
confidence: 99%